Pattern multiplicity and fumarate hydratase (FH)/S-(2-succino)-cysteine (2SC) staining but not eosinophilic nucleoli with perinucleolar halos differentiate hereditary leiomyomatosis and renal cell carcinoma-associated renal cell carcinomas from kidney tumors without FH gene alteration. (June 2018) - Muller, Marie; Guillaud-Bataille, Marine; Salleron, Julia; Genestie, Catherine; Deveaux, Sophie; Slama, Abdelhamid; Paillerets, Brigitte; Richard, Stéphane; Benusiglio, Patrick; Ferlicot, Sophie
Abstract Hereditary leiomyomatosis and renal cell carcinoma syndrome is characterized by an increased risk of agressive renal cell carcinoma, often of type 2 papillary histology, and is caused byFH germline mutations. A prominent eosinophilic macronucleolus with a perinucleolar clear halo is distinctive of hereditary leiomyomatosis and renal cell carcinoma syndrome-associated renal cell carcinoma according to the 2012 ISUP and 2016 WHO kidney tumor classification. From an immunohistochemistry perspective, tumors are often FH-negative and S-(2-succino)-cysteine (2SC) positive. We performed a pathology review of 24 renal tumors in 23FH mutation carriers, and compared them to 12 type 2 papillary renal cell carcinomas fromFH wild-type patients. Prominent eosinophilic nucleoli with perinucleolar halos were present in almost allFH -deficient renal cell carcinomas (23/24). Unexpectedly, they were also present in 58% of type 2 papillary renal cell carcinomas from wild-type patients. Renal cell carcinoma in mutation carriers displayed a complex architecture with multiple patterns, typically papillary, tubulopapillary, and tubulocystic, but also sarcomatoid and rhabdoid. Such pattern diversity was not seen in non-carriers. FH/2SC immunohistochemistry was informative as all hereditary leiomyomatosis and renal cell carcinoma-associated renal cell carcinomas were either FH− or 2SC+. For FH and 2SC immunohistochemistries taken separately, sensitivity of negative anti-FH immunohistochemistry was 87.5% and specificity was 100%. For positive anti-2SC immunohistochemistry, sensitivity, and specificity were 91.7% and 91.7%, respectively. AllFH wild-type renal cell carcinoma were FH-positive, and all but one were 2SC-negative. In conclusion, multiplicity of architectural patterns, rhabdoid/sarcomatoid components and combined FH/2SC staining, but not prominent eosinophilic nucleoli with perinucleolar halos, differentiate hereditary leiomyomatosis and renal cell carcinoma-associated renal cell carcinoma from type 2 papillary renal cell carcinoma with efficientFH gene. Our findings are crucial in identifying who should be referred to Cancer Genetics clinics for genetic counseling and testing.